Pharmacological profile of 2-bromoterguride at human dopamine D 2, porcine serotonin 5-hydroxytryptamine 2A, and α 2C-adrenergic receptors, and its antipsychotic-like effects in rats - Jantschak, Florian; Brosda, Jan; Franke, Robert T.; Fink, Heidrun; Möller, Dorothee; Hübner, Harald; Gmeiner, Peter; Pertz, Heinz H. (Journal of Pharmacology and Experimental Therapeutics, 2013)
Dopaminergic, serotonergic, and adrenergic receptors are targets for therapeutic actions in schizophrenia. Dopamine D receptor partial agonists such as aripiprazole represent a treatment option for patients with this severe disorder. The ineffectiveness of terguride, another D receptor partial agonist, in treating schizophrenia was recently attributed to its considerably high intrinsic activity at D receptors. In this study, we used functional assays for recombinant D receptors and native 5-hydroxytryptamine 2A (5-HT), α- adrenergic, and histamine H receptors to compare the pharmacological properties of terguride and three of its halogenated derivatives (2-chloro-, 2-bromo-, 2-iodoterguride) with those of aripiprazole. Subsequently, we studied the antidopaminergic effects of 2-bromoterguride using amphetamine-induced locomotion (AIL). Its influence on spontaneous behavior was tested in the open field. Extrapyramidal side effect (EPS) liability was evaluated by catalepsy test. In a guanosine 5′-O-(3-[S]thio)triphosphate ([ S]GTPγS) binding assay, 2-chloro-, 2-bromo-, and 2-iodoterguride produced intrinsic activities at human D (hD) receptors that were half as high as the intrinsic activity for terguride; aripiprazole lacked agonist activity. 2-Bromoterguride and aripiprazole activated D receptor-mediated inhibition of cAMP accumulation to the same extent; intrinsic activity was half as high as that of terguride. All compounds tested behaved as antagonists at human D /Gα (hD/Gα) receptors. Compared with aripiprazole, terguride and its derivatives displayed higher affinity at porcine 5-HT receptors and α- adrenoceptors and lower affinity at H receptors. 2-Bromoterguride inhibited AIL and did not induce catalepsy in rats. Because of its in vitro and in vivo properties, 2-bromoterguride may be a strong candidate for the treatment of schizophrenia with a lower risk to induce EPS. Copyright © 2013 by The American Society for Pharmacology and Experimental Therapeutics.